Pengaruh Pendapatan Premi, Hasil Underwriting, Hasil Investasi Dan Risk Based Capital Terhadap Laba Perusahaan Asuransi: Indonesia - Fanny Oktivia Denovis; Sari Arsita; Nurhayati Nurhayati (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2022)
This study’s objective is to identify the effect of premium income, investment results, and risk based capital towards the profit of insurance companies period 2015 until 2020. This study is a quantitative-descriptive research, which is a research that defines the characteristics of the variable with the data used numeric form. The population of this study are 15 insurance companies and 6 companies as the sample, which use a non-probability sampling. The sampling technique used in this study is purposive sampling, with the criteria for insurance companies that went go-public and were listed on the Indonesia Stock Exchange in 2015-2020 period and insurance companies that issued financial statements during the 2015-2020 period. Hypothesis testing is done by classic assumption test, multiple linear test, and hypothesis (model accuracy) test.. Data analysis was performed with Statistical Package for the Social Sciences (SPSS) assisted by SPSS Windows Release 24 statistical application to facilitate data processing. The results of this study are that premium income and risk based capital do not significantly affect the profits of insurance companies. Investment results show a significant effect on the profits of insurance companies does not significantly affect the profits of insurance companies. Key Words : Premium Income, Investment Result, Risk Based Capotal, Profit of Insurance Company